2019
DOI: 10.12659/msm.917375
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing of Osteosarcoma Gene Expression Profile Revealed that miR-214-3p Facilitates Osteosarcoma Cell Proliferation via Targeting Ubiquinol-Cytochrome c Reductase Core Protein 1 (UQCRC1)

Abstract: Background Osteosarcoma (OS) is a common primary malignant bone tumor for which the molecular mechanisms remain unclear. Studies on coding and non-coding RNAs are needed to determine the molecular mechanism. Material/Methods To explore the potential roles of miRNAs and mRNA in OS, we determined the miRNA and mRNA expression profile of 3 pairs of OS and paracancerous tissues from patients with OS by sequencing and bioinformatics analysis. The expression levels of critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The abnormal expression of UQCRC1 has been reported in various human cancers. UQCRC1 is upregulated in breast cancer ( 41 ), ovarian cancer ( 41 ), and PC ( 18 ), while downregulated in colorectal cancer ( 16 ), osteosarcoma ( 42 ), and clear cell renal cell carcinoma ( 17 ). To date, the mechanistic studies of UQCRC1 in tumors only focused on the tumor cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of UQCRC1 has been reported in various human cancers. UQCRC1 is upregulated in breast cancer ( 41 ), ovarian cancer ( 41 ), and PC ( 18 ), while downregulated in colorectal cancer ( 16 ), osteosarcoma ( 42 ), and clear cell renal cell carcinoma ( 17 ). To date, the mechanistic studies of UQCRC1 in tumors only focused on the tumor cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…miR-214-3p is one of the miRNAs with oncogene properties that are important in the process of various cancers ( 9 ). The miR-214-3p level is markedly increased in osteosarcoma ( 9 , 10 ). Liver cancer has been shown to have oncogene capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…A later study by the same group confirmed the role of miR-127 and miR-376a in tumour suppression in osteosarcoma cells [ 238 ]. In contrast, osteosarcoma cell proliferation can be enhanced via targeting of ubiquinol-cytochrome c reductase core protein 1 (UQCRC1) with miR-214-3p [ 239 ]. In gastric cancer, the miR-370/UQCRC2 axis positively regulates the epithelial-mesenchymal transition (EMT) signalling that affects tumour proliferation and metastasis [ 240 ].…”
Section: Mirna Regulation Of Mitochondrial Genesmentioning
confidence: 99%